CONDIÇÕES AMBIENTAIS DAS NASCENTES QUE INTEGRAM AS BACIAS HIDROGRÁFICAS DA APA - ESTRADA PARQUE PIRAPUTANGA-MS: CONTRIBUIÇÃO PARA UMA GESTÃO INTEGRADA - IVÂNIA MINEIRO DE SOUZA (2024)
Brazilian legislation supports the preservation of natural vegetation along rivers, around springs and reservoirs, and in permanent protection areas (APP) throughout the territory. Given the environmental importance of this directive, this research proposes a reflection on the preservation of environmental protection areas (APA), focusing on the peculiarities of the APA - Estrada Parque Piraputanga, aiming to contribute to the proposition of actions to mitigate environmental impacts on springs and watersheds and to support the organization, planning, and environmental management. The APA - Estrada Parque Piraputanga was created by State Decree No. 9.937/2000, located along highway 450, extending 42.5 km through the municipalities of Aquidauana and Dois Irmãos do Buriti in the state of Mato Grosso do Sul. The APA covers an area of 10,108 hectares, in a morphoclimatic region with beautiful landscapes on the escarpment of the Maracaju Mountain Range, containing many fishing spots, guesthouses, a winery, and several natural attractions with great tourism potential, such as the Santa Bárbara Mountain Range and the Aquidauana River, which can be characterized as tourism inducers for the region. This research aims to diagnose the environmental conditions and negative impacts related to the anthropic occupation process near the springs that integrate the watersheds of the APA - Estrada Parque Piraputanga. The methodological procedures adopted included a review of existing literature on the study topic, consultation of secondary sources about the research area, field data collection focusing on spring areas, photographic recording, and the use of geotechnologies for mapping the conservation unit's boundaries, locating study points, drainage network, and land use and occupation. The results point to the urgent need for the adoption of mitigating measures for environmental impacts to recover riparian forests and preserve water bodies, especially in spring areas, since the existence of the APA - Estrada Parque Piraputanga Conservation Unit is not fulfilling the objectives of its creation.